DETERMINAN FLUKTUASI HARGA SAHAM SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muljono, Muljono (Jurnal Analisis Bisnis Ekonomi, 2008)
This research is aimed at analyzing influence of several factor on stock price fluctuation of financial sectors on 2004 up to 2005 in BEJ. The research result show that from the six factors assumed to influence on stock price fluctuations of financial sectors under investigation, there are Price Earning Ratio (PER), Earning Per Share (EPS), Book Value (BV), Return on Invesment (ROI), Return on Equity (ROE) and interest rate. The sample was taken by using purposive sampling polling data method. The population cover 130 companie, while the taken sample consist of 42 companies, the research period of 2 years (2004 up to 2005). The data were analyzed by double regression model. It empirically is found taht Earning Per Share (EPS) significant influences on stock price fluctuations. Based on the research result it is also dicovered that Price Earnning Ratio (PER), Earning Per Share (EPS), Book Value (BV), Return on Invesment (ROI), Return on Equity (ROE) and interest rate have weak influencce in explaining stock price fluctuation variation at the Indonesian capital market, in which Adjusted R2 is only 37.7 which the means taht stock price fluctuations is mostly determined by market psycology, that is not fundamental factors.